Flipping heck! (Economist, 2021)
The article focuses on rely of cryptography on numbers for generation of unbreakable keys and mentions project of Codesigned Improved Neural Foundations Leveraging Inherent Physics Stochasticity (COINFLIPS). Topics discussed include addition of random-number-generating unit to yield and supply of randomness in graphic processing units, hardware involving transistors to translate signal into digital bits and collisions generatd by modern colliders.